2010
DOI: 10.4061/2010/582382
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of Adipose Tissue-Derived Insulin-Secreting Mesenchymal Stem Cells and Hematopoietic Stem Cells: A Novel Therapy for Insulin-Dependent Diabetes Mellitus

Abstract: Aims. Insulin dependent diabetes mellitus (IDDM) is believed to be an autoimmune disorder with disturbed glucose/insulin metabolism, requiring life-long insulin replacement therapy (IRT), 30% of patients develop end-organ failure. We present our experience of cotransplantation of adipose tissue derived insulin-secreting mesenchymal stem cells (IS-AD-MSC) and cultured bone marrow (CBM) as IRT for these patients. Methods. This was a prospective open-labeled clinical trial to test efficacy and safety of IS-AD-MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 11 publications
3
71
0
Order By: Relevance
“…However, the use of BMMSCs is still problematic because of the low number of MSCs found in bone marrow aspirates and the invasive procedure associated with obtaining them. When (17) reported that co-transplantation of adipose tissuederived insulin-secreting MSCs and hematopoietic stem cells is beneficial in reducing exogenous insulin requirement in patients with insulin-dependent diabetes mellitus. It has also been demonstrated that transplantation of ADMSCs attenuates diabetic bladder dysfunction and diabetic retinopathy in a diabetic rat model (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of BMMSCs is still problematic because of the low number of MSCs found in bone marrow aspirates and the invasive procedure associated with obtaining them. When (17) reported that co-transplantation of adipose tissuederived insulin-secreting MSCs and hematopoietic stem cells is beneficial in reducing exogenous insulin requirement in patients with insulin-dependent diabetes mellitus. It has also been demonstrated that transplantation of ADMSCs attenuates diabetic bladder dysfunction and diabetic retinopathy in a diabetic rat model (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro functionality of these cells was also confirmed by insulin production and release in a glucose-responsive manner. [4][5][6] We decided to infuse the cells in portal circulation since liver is the most tolerogenic organ 7 . LADA is believed to be an auto-immune disorder and once the cells are infused in to thymus, it helps in preventing the rejection of these cells by inducing central tolerance 8 .…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs have been used in animal models of diabetes as well as a number of human clinical trials (phase I/II) (110). Extensive clinical trials of ADSCs have been performed, and a number of these have entered phase III (39).…”
Section: Introductionmentioning
confidence: 99%